Spatial Determinants of Livestock Depredation and Human Attitude Toward Wolves in Kailadevi Wildlife Sanctuary, Rajasthan, India - Mahajan, Prashant; Chaudhary, Rohit; Kazi, Abduladil; Khandal, Dharmendra (Frontiers in Ecology and Evolution, 2022)
Grey wolves are capable of adapting to human-dominated landscapes by utilizing domestic prey as a source of food. Livestock depredation by wolves incurs heavy economic loss to the villagers, resulting in negative attitudes towards the species and leading to increased conservation conflict. We used multi-state occupancy modelling on the interview data to assess the ecological factors governing livestock depredation by wolves. We also assessed the socio-demographic factors that may govern the attitude of villagers towards the wolf using ordinal regression. Over the past year, 64% of respondents reported loss of livestock, in which goat (63%) comprised the major share, followed by sheep (22%) and cattle calves (15%). Wolves tend to hunt medium-sized domestic prey (sheep and goats) that commonly graze in open agricultural areas. Estimated livestock depredation probability of wolves was 0.84 (SD = ±0.23). Depredation probability was influenced by factors like habitat-use by wolves, extent of agricultural areas, scrubland area, and settlement size. Respondents with prior experience of livestock loss held more negative attitudes. Shepherds held more negative attitudes than other occupations. Increases in the respondent's age and education level reflected a positive shift in attitudes towards the wolf. High economic loss caused by livestock depredation by wolves can lead to retaliatory persecution of wolves. Adequate compensation for livestock loss, along with better education and awareness can help lead to coexistence between wolves and humans in multi-use landscape of Kailadevi Wildlife Sanctuary, Rajasthan.